Cognitive-Behavioral Counseling: A Strategy to Overcome Students’ Addiction to TikTok through Self-Instruction Method - Prayogi, Fiki; Utomo, Prio; Bulantika, Siti Zahra (Jurnal Kajian Bimbingan dan Konseling, 2023)
TikTok has influenced the development of student behavior. Therefore, a service strategy is needed to overcome TikTok addiction in students. This study aimed to determine whether there was a decrease in TikTok addiction in students after being given cognitive-behavioral counseling with the self-instruction method. The researchers employed experimental research with one group pretest-posttest designs as the research design. The research samples consisted of 18 students. The researchers utilized the TikTok addiction scale as the research instrument for collecting the data. The validity result of the instrument was in KMO value of 0.791 with Sig. of 0.000 (0.791 greater than 0.5). The finding of the reliability test in the research instrument was 0.821 based on Alpha coefficient analysis. The researchers employed non-parametric statistics for data analysis of research. Furthermore, the decision H0 is rejected, and H1 is accepted based on the Z value of -2.703 (0.005 less than 0.05) by implementing the Wilcoxon test. Therefore, the results showed that there was TikTok addiction among the students after being given cognitive-behavioral counseling with the self-instruction method. The results of this study contributed as enrichment material both theoretically and practically related to the use of cognitive-behavioral counseling with self-instruction method as the basis for counseling services in schools.